Technology and Justice: A research report by Trinity FLAC - (:unkn) unknown (Trinity Free Legal Advice Centre, 2020)
This report set out to examine technology’s potential to make the law more accessible for those who need legal support. The comprehensive 286-page report focuses on issues such as barriers to justice, the impact of technology on access to justice, some of the ethical concerns regarding legal technology and relevant laws surrounding the subject.
Keywords: Barriers to justice; Technology; Legal technology; Ethics; Law; Artificial intelligence; Human rights; Information technology